Business Ethics and Corporate Governance's Influence on the Sustainability of Family Businesses with Company Size as an Intervening Variable - Erna Setiyawati; Agus Munandar (International Journal of Science and Society, 2023)
The purpose of the study is to examine the influence of business ethics and corporate governance on the sustainability of family businesses, with company size as a mediating variable. The size of the company is a parameter for assessing and determining the scale of the enterprise. The population in this study consisted of 38 companies that were members of the West Java Jamu Entrepreneurs Association. The determination of the number of samples used purposive sampling with criteria in the form of a family business, so that the sample used was 12 family business companies with 48 respondents. Data collection techniques are carried out by using several instruments, namely questionnaires, interviews, and field observations. According to the findings of this study, business ethics has a positive impact on the long-term viability of a family business. Good corporate governance positively affects the sustainability of the family business. Meanwhile, the size of the company also has a positive effect on the sustainability of the family business. The size of the company turns out to be able to mediate relationships in the mediation variable; the size of the company is able to influence business ethics on the sustainability of the family business, while the mediation variable shows the size of the company is able to also influence Good corporate governance is important for the sustainability of the family business. The findings of this study provide useful information for herbal medicine company owners related to the influence of the variables studied. These findings are useful for employers to better understand the dynamics of family business sustainability in promoting business ethics, good governance, and company size.